Abdominal pain, cramping or discomfort impairs quality of life in women: An internet-based observational pilot study focussing on impact of treatment - Enck, Paul; Koehler, Ursula; Weigmann, Harald; Mueller-Lissner, Stefan (Zeitschrift für Gastroenterologie, 2017)
Background Abdominal pain, cramping, and discomfort (APCD) are experienced by up to 30 % of adults in Europe.Objective To assess the impact of APCD on quality of life (QoL) and to investigate the effectiveness, tolerability, and impact on QoL of hyoscine butylbromide (HBB, Buscopan®) compared with STW 5 (Iberogast®) or analgesics in women with APCD.Methods An internet-based observational pilot study was conducted in Germany in women who had predominantly used HBB, STW 5, or analgesics (n = 240 per treatment) to treat APCD. This online survey included questions on QoL, effectiveness, and tolerability.Results A total of 720 completed questionnaires was evaluated. APCD had a major impact on QoL, with 96 % of women reporting that daily activities were disrupted at least sometimes, and 44 % at least often. Other aspects of QoL, such as quality of work, eating habits, and social activities, were also affected in most women. After taking their medication of choice, 91 % of women in the HBB group reported they could “very often” or “often” continue with their daily activities, compared with 84 % and 85 % in the STW 5 and analgesic groups, respectively (p < 0.05 for both comparisons). HBB was perceived to be the “best solution” to overcome APCD symptoms “very often” or “often” by more women (86 %) than STW 5 (75 %) and analgesics (74 %) (p < 0.05 for both comparisons).Conclusion Women with APCD have impaired QoL. All treatments were considered effective by the majority of participants. Compared with STW 5 or analgesics, HBB was reported to facilitate return to daily activities more frequently.
Keywords: Abdominale Schmerzen; Krämpfe; Butylscopolaminbromid; Patientenbefragung; Lebensqualität